Tannic Acid-induced Modulation of Poly(ADP-Ribose) Glycohydrolase and NAD+ Content in Rat Liver and Thymocyte Nuclei - Asatryan, Anush L. (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The goal of the present study was to determine whether the treatment of intact rats with tannic acid (TA) could alter activities of the main players in poly(ADP-ribose) (PAR) polymers turnover. Materials and Methods: Animals were treated according to the regulations of the National Center of Bioethics (Armenia). Cell nuclei were isolated according to standard procedure. PAR polymerase 1 (PARP 1) activity was evaluated by NAD+ consumption. PAR glycohydrolase (PARG) protein was estimated by sandwich ELISA method. Data are expressed as mean Â± standard deviation (SD). Statistical differences in the results between groups were evaluated by the Studentâ€™s t-test. P < 0.05 was considered statistically significant. Results: The results demonstrate relatively stable stimulation of PARP 1 activity in liver and thymocyte nuclei of rats treated with TA. TA stimulated PARP 1 activation in thymocyte and liver nuclei is paralleled with drop in NAD+ content for more than 30% below basal level. The concentration of PARG in liver nuclei exceeded the basal value of PARG content in thymocyte nuclei nearly 3.5-fold. In 24 h after administration of TA to animals the content of PARG protein in thymocyte nuclei decreased by 30%. Decrease of PARG content in liver nuclei was more substantial and proceeded for 48 h after the treatment of rats with TA. Conclusion: TA-induced stimulation of PARP 1 in liver and thymocyte nuclei paralleled with decrease in NAD+ and PARG content could alter PAR polymer turnover and mediate genotoxic effect of TA revealed by light microscopy examination of liver.